The Relationship Between Literacy Sklls and Scientific Explanation on Students Scientific Reasoning Throught Reading Concept Map-Numbered Head Together Learning Model - irawan, Ferry; Pertiwi, Sri Ananda; Zakiyah R, Nur; A, Henita (Journal of Biology Learning, 2025)
Literacy skills play an important  role in helping students clarify basic concepts, build relationships between concepts, reason and test each detail of each interrelated information and are able to derive each concept, thus students are accustomed to understanding each scientific process and activity carried out in Biology learning. The relationship between these two skills trains students to actively carry out in-depth scientific investigations.The purpose of this study was to identify the relationship between scientific literacy skills and scientific explanation skills in empowering scientific reasoning skills through the application of the Remap-NHT (Reading Concept Map-Numbered Head Together) learning model. This study included a quasi-experiment using a non-equivalent pretest-post-test control group design with a total sample of 85 eleventh grade students in the Natural Sciences department at SMAN 4 Malang in the 2023/2024 academic year. The population was distributed into 3 groups. Scientific literacy skills and scientific reasoning skills were assessed using an essay test, while scientific explanation skills were assessed using an assessment rubric. Data analysis was tested using multiple regression analysis. The results showed that (1) there was a significant relationship between scientific literacy skills and scientific reasoning skills; (2) there is a significant relationship between scientific explanation skills and scientific reasoning skills; and (3) there is a significant relationship between scientific literacy skills and scientific explanation skills that have an integral effect on scientific reasoning skills. The interrelationship between scientific literacy skills, scientific explanation skills and scientific reasoning skills can be observed in the regression equation Y = 0.317 * X1 + 0.995 * X2 + 30.113. Based on the findings, it is concluded that Remap-NHT is able to improve students' scientific literacy skills, scientific explanation skills, and scientific reasoning skills, the interrelationships of which influence each other.